Vínculo como dimensão da longitudinalidade na estratégia saúde da família - PINHEIRO, Siane Rocha de Almeida (2012)
Introduction: Networks of health care proposals to reorganize the healthcare model should be coordinated by the Primary Health Care. To fulfill this role, she must have quality. Starfield (1992) taken as starting point for evaluation of Primary Care in defining the essential attributes being longitudinality one. The conceptual limitations of this attribute and the lack of methods to evaluate it is a consensus in the literature. Therefore, it seems more reasonable to assess interpersonal bonding, because it reflects the quality of the relationship between users and professionals. Objective: To evaluate the relationship between staff and users, according to the perceptions of managers, professionals and users of the Family Health Program in São Luís. Methods: 882 users were selected by simple random sampling and distributed in 20 Family Health Units drawn. Also participating were 80 professionals and 32 managers of the Health Family. Was used PCATool adapted to Brazil. Quantitation was performed by evaluation scores, which could range 1-6 and by Likert scale. The tests used were Kruskal-Wallis and chi-square. Results: The Composite Index of the Bond was 4,44 for users, 4,62 for professionals and 4,77 for managers, and its acquisition of 41% to 60% of its total. The Kruskal-Wallis test showed that there was no disagreement between the three research subjects and chi-square test showed that the evaluation of general users was the best. Conclusion: The Composite Index of the contract obtained in this study suggests an extension in the Primary Care to improve, with no difference between the perceptions of the subjects evaluated. This information reflects how fragile is the relationship between professionals and users and the inadequacy of the service to take over the coordination of the system. It also reinforces the importance of putting the issue on the agenda for discussion of the Primary Care Management of the Municipality of Sao Luis by relevance.